Studies on high frequency performance of advanced Si MOSFETs - Sun, Zhiyong. (2009)
This final year project studied degradation mechanisms contributing to the increased high frequency noise of deep-submicrometer nMOSFETs after different hot-carrier (HC) stresses. An HP4156B semiconductor parameter analyzer was used for dc measurement and HC stress. Three groups of devices were stressed for RF noise characterization. Hot carrier stresses with drain avalanche hot carrier stress (Vgs = 1.5 V, Vds = 3 V), channel hot electron stress (Vgs = 1.5 V, Vds = 3 V) and hot hole injection (Vgs = 0.4 V, Vds = 3 V) were carried out respectively to investigate the degradation mechanisms of high frequency noise.